Immune Responses to Non-Tumor Antigens in the Central Nervous System - Huber, Amanda K.; Duncker, Patrick C.; Irani, David N. (Frontiers in Oncology, 2014)
The central nervous system (CNS), once viewed as an immune privileged site protected by the blood-brain barrier (BBB), is now known to be a dynamic immunological environment through which immune cells migrate to prevent and respond to events such as localized infection. During these responses, endogenous glial cells, including astrocytes and microglia, become highly reactive and may secrete inflammatory mediators that regulate BBB permeability and recruit additional circulating immune cells. Here, we discuss the various roles played by astrocytes, microglia, and infiltrating immune cells during host immunity to non-tumor antigens in the CNS, focusing first on bacterial and viral infections, and then turning to responses directed against self-antigens in the setting of CNS autoimmunity.